Thermoelectric microstructures of Bi2Te3/Sb2Te3 for a self-calibrated micropyrometer - Gonçalves, L. M. (2006)
The fabrication of thermopiles suitable for thermoelectric cooling and energy generation using Bi2Te3 and Sb2Te3 as n- and p-type layers, respectively, is reported. The thin-film thermoelectric material deposition process, thin-film electronic characterization and device simulation is addressed. The thermoelectric thin-films were deposited by co-evaporation of Bi and Te, for the n-type element and Sb and Te, for the p-type element. Seebeck coefficients of −190 and +150 uVK−1 and electrical resistivities of 8 and 15 uOhm.m were measured at room temperature on Bi2Te3 and Sb2Te3 films, respectively. These values are better than those reported in the literature for films deposited by co-sputtering or electrochemical deposition and are close to those reported for films deposited by metal-organic chemical vapour deposition and flash evaporation. A small device with a cold area of 4mm×4mm and four pairs of p–n junctions was fabricated on a Kapton® substrate, showing the possibility of application in Peltier cooling, infrared detection and energy generation. Small devices fabricated on a polyimide (Kapton®) substrate and micro-devices fabricated on a silicon nitride substrate were simulated using finite element analysis. The simulations show the possibility of achieving near 20K cooling over 1mm2 areas.